Design and investigation of dual-layer electrodes for proton exchange membrane fuel cells - Zhao, B.; Sun, L.; Ran, R.; Shao, Zongping (Elsevier, 2014)
With an aim to develop a proton-exchange-membrane fuel cell (PEMFC) with improved water management, catalyst-coated membranes based upon Nafion 212 membrane with electrodes of dual-layer structure which consist of one hydrophilic layer of Pt/C + Nafion and one hydrophobic layer of Pt/C + PTFE arranged in a proper order, is specifically designed and successfully fabricated by a facile high-temperature spray deposition technique. Dual-layer structured anode and cathode are separately evaluated by electrochemical performance in single cells. Effect of relative thickness of the dual layers in the electrode on the cell performance is investigated. No improvement in cell performance is observed by adopting the dual-layer structure for the anode as compared to conventional anode with single hydrophilic catalyst layer. However, better cell performance is observed for the cell with dual-layer structured cathode, and the optimal cell reaches a peak power density of about 800 mW cm- 2 at 50 °C with humidified hydrogen and oxygen as fuel and oxidant respectively. © 2013 Elsevier B.V.